Enacting play: performance within the public domain - Moys, Anthea Julian Dineo (My University, 2009)
ABSTRACT In this thesis I explore play as enacted in certain forms of performance art presented in the public sphere. I take as my premise the notion that play is a primary form of creativity fundamental to the healthy development of ‘the self’ and community. I draw on the theories of Donald Winnicott (1971) and Johan Huizinga (1970) to explore the historical sources of play theory and connect these to contemporary play concepts articulated by Pat Kane (2004) et al. I argue for the relevance of play (theory and enactment) to contemporary performance art, specifically the type that emphasizes the action of the performance as meaningful over its material documentation. Such performance questions frameworks of visual art and its objects. International artists, Tino Sehgal and Gustavo Artigas, epitomize this type of performance and I discuss their work accordingly. Their practice entails taking up a different subject position to the conventional role of artist in that they direct their performances rather than enact them; they orchestrate others in their interventions. Many of their performances seem pointless and irrational but they use these concepts to address the growing alienation of the postmodern subject by challenging economic and cultural values of ‘the west’ that are antithetical to the values of play. By drawing on the theories of play and exploring the work of the abovementioned artists in relation to instances of performance art in a local (South African) context, I aim to open a space for articulating the relevance of play to a local situation which has, because of its history, arguably not had the chance to play. I refer to my own artistic practice in this context.